Prosodic Morphological Analysis on Blends Used as Brand of Snacks And Beverages - Ratna Setyowati (Lexicon, 2015)
This research focuses on the blends used in the brands of snacks and beverages which are found in supermarkets around Yogyakarta. More specifically, it attempts to identify and classify blend into four structural formations using prosodic morphology approach. The syllabic constituents of each source word and the number of syllables of the blends are also analyzed in this research. The findings of this research show that coining each beginning of two words is the structural formations of blends mostly used in the data collected (9 blends). It is followed by coining beginning and ending elements of word (7 blends), coining two words that have common sequence sounds (6 blends), and ended by coining two words that have multiple sounds (3 blends). The structural formations that are mostly relevant to the size of blends based on the number of syllables of the second source wordsis AD formation (83.33%). It shows that the structures of blends without overlapping on the source words are more relevant to the theory of size of the blends than the structures of blends with overlapping.